ANALISIS PERAN AKTOR DALAM PEMEKARAN KABUPATEN BREBES - Trisnawati, Akhpriyani; ., Fitriyah; Setiyono, Budi (Journal of Politic and Government Studies, 2015)
ABSTRACTIONOpportunities of the policy about the expansion which protected by UU No. 32 of 2004 article 4-8 and PP No. 78 of 2007 made a lot of local and regional elites take an advantage of these opportunities, as well as the southern of Brebes region. The expansion discourse that several years dim come back arise after the election 2012. Although, the pros and contras coloring of the expansion discourse in brebes regency, but the expansion cannot be happened without the actors role to achieve expansion. Therefore, the formulation of the problem in this this research is "Who are the actors involved in the expansion plan of Brebes regency?", "What did the actors do in the expansion plan of Brebes regency ?" and "What is the purpose to be achieved from the expansion of Brebes?".This research aims to identify the actors and their activities in the expansion plan of Brebes regency and the goals of the expansion. The method used is descriptive qualitative. The primary data source was obtained through interview with snowball sampling technique, and secondary data from document, archive and other sources related to the research. Analysis techniques using analysis of qualitative data which is the analysis in the form of description, illustration and drawing conclusions on the problem analysed.From the results of this research, be discovered that the idea of expansion of Brebes regency is already discussed in 1963 by H.S.A Basori, a member DPR-GR of the Brebes District. Post-reform, demands of expansion continued by other South Brebes figures consisting of religious leaders / organizations, politicians, academics and NGO activists, Head of the Village and BPD. In the struggle, the actors make a structure dan give a socialization. While the path used is Informal and Formal. The purpose is effective and efficient services, accelerate development, manage and develope a potential in the south region, ease community control to governance, get a central funding and economic motives.The suggestion that can be given, among others; actor to continue to comply with Regulation 78 of 2007 in the process of expansion, don't leave the relevant institutions such as camat, and had to leave his ego so that the expansion process can be done well. While the recommendation for next researcher are able to see from the side of the internal conflict in the stewardship and how the readiness of the southern region community if the expantion is really happening.Keywords: Expansion, actor, role.